Health Literacy for Clerkship Students - Kimberly Zoberi; Kelly Everard; James Deckert; Laura Frankenstein (Association of American Medical Colleges, 2008)
Abstract Low literacy is an underrecognized problem in health care today. Given the tremendous impact of health literacy on patient outcomes, health literacy training should be included in medical school curricula. Medical students and residents are the ideal learning groups for this material because of the large impact of this knowledge across many years of medical practice and because they may be more open to communication skills training. Based on a presentation by the AMA Foundation, we designed an interactive workshop to introduce medical students to the issues of low literacy and its health care impacts. The workshop includes sensitizing students to the experience of the low-literacy patient, illustrating the prevalence of the problem and its consequences to patient outcomes, and role-playing the teach-back method to enhance patient communication. The following is an approximate schedule for this 90-minute workshop: sensitization exercise and brief discussion-10 minutes; introduction to health literacy, prevalence, and consequences-10 minutes; video presentation-20 minutes; teach-back exercises-30 minutes; Taboo-style word game-10 minutes; and student feedback and suggestions for improvement-10 minutes. Student response to this workshop has been positive. Students have reported an increased awareness of low health literacy as a barrier to patient care. Students also have appreciated the opportunity to practice the teach-back skill in a nonthreatening environment.